Pelatihan Manajemen Keuangan Syariah untuk Pengelola Masjid dan Organisasi Sosial Keagamaan - Anisatul Maghfiroh (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
Sharia Financial Management Training for Mosque Managers and Religious Social Organizations aims to improve the understanding and skills of mosque managers and religious social organizations in managing finances according to sharia principles. This research was conducted with a theory and practice-based training approach, involving 30 mosque managers and religious social organizations in X area. The method used was interactive training with material on sharia financial management, case studies, and simulations. The results showed that the training participants experienced a significant increase in their understanding of sharia-based management of mosque funds, including in terms of budget planning, financial recording, and transparent financial reports. In conclusion, this training has a positive impact on more effective financial management in accordance with sharia principles in mosques and social religious organizations.